Attentional bias and executive control in treatment-seeking substance-dependent adolescents: A cross-sectional and follow-up study. (1st February 2016) - van Hemel-Ruiter, Madelon E.; Wiers, Reinout W.; Brook, Frank G.; de Jong, Peter J.
Highlights: Substance dependent adolescents showed heightened attentional bias for substance cues. Substance related attentional bias was associated with severity of dependence. Substance dependent adolescents did show a tendency towards a lowered executive control. Six months after treatment entrance there were no significant changes in attentional bias, executive control, substance use or severity of dependence. Abstract: Background: Research in adults shows that substance dependent individuals demonstrate attentional bias (AB) for substance-related stimuli. This study investigated the role of AB in adolescents diagnosed with alcohol, cannabis, amphetamine or GHB dependency on entering therapy and six months later, and the role of executive control (EC) as a moderator of the relationship between problem severity and AB. Methods: Seventy-eight young substance-dependent (SD) patients (mean age = 19.5), and 64 healthy controls (HC; mean age = 19.0) were tested. Thirty-eight SD patients took part at 6-month follow-up (FU). AB was indexed by a visual probe task, EC by the attention network task, problem severity by the short alcohol (or drug) use disorder identification test and the severity of dependence questionnaire. Results: SD patients demonstrated an AB for substance stimuli presented for 500 ms and 1250 ms, with the latter related to severity of dependence. There was a nonsignificant tendency indicating that EC was higher in HC than SD participants, but EC did not moderate the relationship between AB and dependency. Substance use, dependency, EC and AB remained unchanged in the 6 month FU period. Conclusions: Young SD patients showed a stronger relatively early as well as maintained AB toward substance cues. A stronger maintained attention was related to higher severity of dependence. Further, there were some indications that EC might play a role in adolescent substance use. The finding that at FU AB and problem severity were not decreased, and EC was not increased underlines the persistent character of addiction.